MEASURING POVERTY AMONG ELDERLY MALAYSIANS - Masud, Jariah; Hamid, Tengku Aizan; Haron, Sharifah A. (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Poverty among the elderly should be measured using different methodology as to differentiate them based on the different dimensions of poverty and to reflect the true differences in needs and resource insufficiency among elderly. How poverty is measured will influence coverage of programs for older persons and to date no specific measurement is available to determine poverty among older persons. This paper is focus on poverty measurement among elderly in Malaysia. Household income data 2009/10 obtained from the Department of Statistic Malaysia were utilized to examine the incidence of poverty among older persons in Malaysia. Incidence of poverty among older persons was measured using two measurements; absolute poverty (Yearly Poverty line income (PLI) of RM8640) and relative poverty (Half Median income of Malaysia of RM21756). Two income measurements were compared; individual elderlyincome and income of households headed by older persons. Measuring poverty using individual income will support the philosophy of economic empowerment of older persons. Income of household headed by older persons will reflectthe economic situation of household headed by older persons, the proportion expected to increase in the future. Data of the study comprised of 184,447 individual member records of which 16325 were those age 60 and older (8.85%). There was also information on 43026 households, 7892 of which are headed by those ages 60 and older (18.3%). The incidence of absolute and relative poverty using the two measurements will be calculated and the implications of such measurement will be discussed.